The effects of quenching and aging on the mechanical and physical properties of recycled aa6061 aluminum chips - Samsi, Mohd Arif (2017)
At present, the usage of aluminum is widely used. The recycling process is needed to respond to the government's call for a green earth campaign cause of the lack of mineral resources on this earth. The direct recycling method is one of the recycling method to reduces cost and energy consumptions. The aim of this study to determine the effects of quenching and aging on mechanical and physical properties of recycled AA6061 aluminum chips. Subsequent from this, the optimum of quenching and aging time and also the mechanical and physical properties were studied . In this study, the surface morphology on the specimen shows a positive results through the length of porous become smaller. The best porosity, density and water absorption is 1.95%, 2.55 g/cm3 and 0.77 %. On the micro-hardness Vickers, the increasing percentage of the micro-hardness is about 19% from a preference value. Meanwhile, for the compression strength the increasing percentage of the compression strength is 17% also from a preference value. From all data were obtain, the optimum quenching and aging time is 8 hours quenching and 10 hours of aging. With this optimum, the reducing of energy consumptions and cost will be obtain.